2017
DOI: 10.1192/apt.bp.115.015610
|View full text |Cite
|
Sign up to set email alerts
|

Functional near-infrared spectroscopy in psychiatry

Abstract: SummaryFunctional near-infrared spectroscopy (fNIRS) has been used in healthcare and medical research for the past two decades. In particular, the use of fNIRS in academic and clinical psychiatry has increased rapidly owing to its advantages over other neuroimaging modalities. fNIRS is a tool that can potentially supplement clinical interviews and mental state examinations to establish a psychiatric diagnosis and monitor treatment progress. This article provides a review of the theoretical background of fNIRS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…In addition, studies of different indoor plants are warranted. Functional near‐infrared spectroscopy (fNIRS) is a non‐invasive neuroimaging technology that maps the functions of the cerebral cortex by measuring hemodynamics and demonstrates cost‐effectiveness (Lai, Ho, Lim, & Ho, ). A recent fNIRS study showed that urban scene led to significant increase of oxyhemoglobin on the right area of the prefrontal cortex as compared to the garden scene (Yu, Ang, Ho, Sia, & Ho, ) and further research is required to assess the effect of plant viewing by fNRIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies of different indoor plants are warranted. Functional near‐infrared spectroscopy (fNIRS) is a non‐invasive neuroimaging technology that maps the functions of the cerebral cortex by measuring hemodynamics and demonstrates cost‐effectiveness (Lai, Ho, Lim, & Ho, ). A recent fNIRS study showed that urban scene led to significant increase of oxyhemoglobin on the right area of the prefrontal cortex as compared to the garden scene (Yu, Ang, Ho, Sia, & Ho, ) and further research is required to assess the effect of plant viewing by fNRIS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the psychological benefits of greenery for older adults are significant (i.e., decreased anxiety), and an indoor green environment can enhance spiritual health (Qin, Sun, Zhou, Leng, & Lian, 2014 (Lai, Ho, Lim, & Ho, 2017). A recent fNIRS study showed that urban scene led to significant increase of oxyhemoglobin on the right area of the prefrontal cortex as compared to the garden scene (Yu, Ang, Ho, Sia, & Ho, 2017) and further research is required to assess the effect of plant viewing by fNRIS.…”
Section: Discussionmentioning
confidence: 99%
“…This study should be replicated with other novel neuroimaging modalities. Functional near-infrared spectroscopy (fNIRS) is noninvasive neuroimaging that maps the functions of the cerebral cortex by measuring hemodynamics and is cost-effective [14]. fNIRS has the advantage of being readily translated to clinical use as it is more cost-effective than functional magnetic resonance imaging (fMRI) [15].…”
Section: Discussionmentioning
confidence: 99%
“…fNIRS is an innovative neuroimaging technique that has a similar mechanism of action to functional MRI (fMRI) [ 30 ], which exploits the different absorption spectra of oxygenated and deoxygenated hemoglobin in the near infrared region to measure alterations in the oxygenated (oxy-Hb) and deoxygenated (deoxy-Hb) hemoglobin concentrations, thereby reflecting regional cerebral blood flow. It is based on an underlying mechanism known as neurovascular coupling, whereby activation of a brain region is represented by an increase in oxy-Hb and a corresponding decrease in deoxy-Hb levels [ 31 ]. However, unlike fMRI, fNIRS allows us to conduct the scan in a naturalistic environment, is relatively insensitive to movement artifacts, and can be done quickly, which makes it more tolerable for our patient.…”
Section: Discussionmentioning
confidence: 99%